Novel QTL Conferring Phosphorus Acquisition and Utilization Efficiencies in Barley - Gao, Shangqing; Xia, Jiaqi; Yuan, Shu; Shen, Youjie; Zhong, Xinting; Zhang, Senfeng; Li, Yuhang; Hu, Deyi; Zeng, Jian; Lan, Ting; Liu, Yaxi; Chen, Guangdeng (Frontiers in Genetics, 2020)
Phosphorus (P) deficiency in agricultural soil is a major constraint for crop production and increasing P acquisition efficiency (PAE) of plants is considered as one of the most cost-effective solutions for yield increase. The objective of this study was to detect quantitative trait loci (QTL) controlling (PAE) and P utilization efficiency (PUE) in barley under applied (+P) and non-applied P (-P) conditions. Based on the analysis of a recombinant inbred lines (RILs) population derived from a cross between a variety and a wild barley accession, 17 QTL controlling PAE, PUE and yield traits were detected. The phenotypic variation explained by each of these QTL ranges from 11.0% to 24.7%. Significant correlation was detected between most of P-related traits and yield traits. Five QTL clusters were identified on four different chromosomes (1H, 3H, 5H and 7H). Two of the QTL clusters, located on chromosome 1H (for GPUP/PUP) and 7H (for SPUE/SPC), respectively, are novel. Fourteen genes located in the interval harboring the major QTL were identified as candidates associated with P efficiency. The stable QTL for PAE, PUE and yield-related traits could be important for breeding P-efficient barley varieties.